Impact of Intravenous Bolus Norepinephrine versus Ephedrine on Post-Spinal Hypotension during Cesarean Section in Libyan Patients - Fathi Abulifa; Ibrahim Garta; Elsonosi Elferjani; Abdalrahman Elzufri; Omar Danfour; Ahmed Aniba; Omar Alhaddad (Khalij-Libya Journal of Dental and Medical Research, 2025)
Spinal anaesthesia-induced hypotension (SAIH) is a frequent and significant complication during Cesarean section (CS) performed under neuraxial blockade, with the potential to cause adverse maternal and neonatal outcomes. The main management involves administration of vasopressors such as Ephedrine (EP) and phenylephrine. Recently, Norepinephrine (NE) has gained considerable attention as a viable alternative due to its favorable hemodynamic profile. This study was conducted to compare the efficacy and safety of NE versus Ephedrine for the treatment of established SAIH in a specific cohort of Libyan patients undergoing CS. This retrospective comparative study included 120 female patients undergoing elective CS under spinal anesthesia, randomized into two groups (n=60 each): the Norepinephrine (NE) group received 8 µg bolus of NE, and the ephedrine (EP) group received 10 mg bolus of Ephedrine (EP) for treating hypotension (Systolic Blood Pressure (SBP) < 90 mmHg or a 20% decrease from baseline). Hemodynamic parameters (SBP, Diastolic Blood Pressure (DBP), Mean Arterial Pressure (MAP), and Heart Rate (HR)) were recorded every 5 minutes from baseline (0 min) up to 60 minutes. Maternal side effects (nausea/vomiting, bradycardia) and neonatal Apgar scores at 1 and 5 minutes were also recorded. Baseline characteristics were comparable between the two groups. The Norepinephrine (NE) group showed significantly higher MAP and SBP values during the initial 20 minutes post-spinal block compared to the Ephedrine (EP) group (e.g., MAP at 5 min: NE 85.27 ± 15.63 mmHg vs. EP 74.82 ± 12.47 mmHg, P < 0.001). The EP group exhibited a significantly higher HR throughout the 60-minute monitoring period (e.g., HR at 10 min: NE 83.35 ± 18.19 bpm vs. EP 107.15 ± 14.88 bpm, P < 0.001). The incidence of maternal bradycardia was significantly higher in the NE group (25.0%) compared to the EP group (1.7%, P < 0.001). The incidence of nausea and vomiting was similar (NE 53.3% vs. EP 58.3%, P = 0.713). Neonatal Apgar scores at 1 and 5 minutes were comparable between the two groups (P > 0.05). Intravenous bolus norepinephrine was more effective than ephedrine in maintaining maternal blood pressure (MAP and SBP) during the critical period following spinal anesthesia for Cesarean section. However, Norepinephrine was associated with a higher incidence of maternal bradycardia. Both vasopressors demonstrated comparable neonatal outcomes.